The Experimental Survey on Role of Gamification on Employee Loyalty and Motivation - Aboalhassan Hosseini; Mehdi raoof (مطالعات مدیریت بهبود و تحول, 2019)
This research has been done to investigate the effect of gamification on employees' motivation and loyalty. This work is a strategic, experimental and applied research and the data have been collected using a questionnaire. The statistical population of this research includes all Babolsar branch of Family clothing (Yalit) sales staff in 2018. All sale staffs were questioned in this study, in which 15 of them were in the experimental group and 15 were in the control group. At first, each group was subjected to pretest and then, the gameplay test was performed for a week and at the end, a post-test was performed. In this research, gameplay was considered as an independent variable and motivation and loyalty were considered as dependent variables. To test the research hypotheses, Unpaired or paired test or paired was used. The results showed that the use of gamification had a positive effect on the motivation of sales staff. In the second hypothesis, the result showed that the gamification has a significant positive effect on the employee's loyalty.